Osip Mandel'štam: i Quaderni di Mosca - Napolitano, Pina (Biblioteca di Studi Slavistici, 2017)
The volume presents a critical reading of the Moscow notebooks by Osip Mandel'štam. The poems are analysed one by one in chronological order, verse by verse, and are accompanied by an interlinear translation. Special attention is paid to their arrangement in poryvy, "impulses" embracing and connecting several compositions, and to their connection with the Mandel'štamian contemporary prose. The aim is to offer on the one hand a support for the reading of the verses, on the other an interpretative glimpse of the work of the late Mandel'štam as a whole.